2001
DOI: 10.1002/net.1036
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost minimum‐time line‐broadcasting schemes in complete binary trees

Abstract: Broadcasting is the process of transmitting a message from a member in a network (originator) to all other members. A line-broadcasting scheme allows two members to communicate during one time unit as long as there is a path of lines between them and no link is used in more than one call between two members. Farley [3] showed an algorithm that accomplishes line broadcasting in any tree on n vertices in minimum time, which is log 2 n n n time units. Since the structure of the tree is unknown in advance, the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In this article, (for k 3 ) and in (for k = 2) it was shown that the cumulative cost of line‐broadcast, from any originator in a k ‐ary tree, is O ( n ). Thus, in addition to the problem we posed at the beginning of our article we pose the following conjecture.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In this article, (for k 3 ) and in (for k = 2) it was shown that the cumulative cost of line‐broadcast, from any originator in a k ‐ary tree, is O ( n ). Thus, in addition to the problem we posed at the beginning of our article we pose the following conjecture.…”
Section: Discussionmentioning
confidence: 95%
“…Averbuch et al studied line‐broadcasting in complete binary trees. They provided a minimum‐time line‐broadcasting scheme originating from any vertex of the tree.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An available path is defined as any simple path in which none of the edges are involved in another call. Some examples in which line broadcasting schemes have been investigated include cycles [KP98], grids [W99] and complete binary trees [AGR01].…”
Section: Related Workmentioning
confidence: 99%